Defining and using evidence in conservation practice. Issue 5 (9th April 2019) - Salafsky, Nick; Boshoven, Judith; Burivalova, Zuzana; Dubois, Natalie S.; Gomez, Andres; Johnson, Arlyne; Lee, Aileen; Margoluis, Richard; Morrison, John; Muir, Matthew; Pratt, Stephen C.; Pullin, Andrew S.; et al.
Abstract : There is growing interest in evidence‐based conservation, yet there are no widely accepted standard definitions of evidence, let alone guidance on how to use it in the context of conservation and natural resource management practice. In this paper, we first draw on insights of evidence‐based practice from different disciplines to define evidence as being the "relevant information used to assess one or more hypotheses related to a question of interest." We then construct a typology of different kinds of information, hypotheses, and evidence and show how these different types can be used in different steps of conservation practice. In particular, we distinguish between specific evidence used to assess project hypotheses and generic evidence used to assess generic hypotheses. We next build on this typology to develop a decision tree to support practitioners in how to appropriately use available specific and generic evidence in a given conservation situation. Finally, we conclude with a discussion of how to better promote and enable evidence‐based conservation in both projects and across the discipline of conservation. Our hope is that by understanding and using evidence better, conservation can both become more effective and attract increased support from society.